Manajemen Sarana dan Prasarana dalam Meningkatkan Proses Pembelajaran di Sekolah Menengah Pertama - Nurmalasari, Ita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Facilities and infrastructure are important components in determining the success of the educational process and one of the factors for improving the quality of education in Indonesia. The importance of educational facilities and infrastructure makes every educational institution make maximum efforts to meet the standards of educational facilities and infrastructure to improve the quality of the learning process. This study uses a qualitative approach with descriptive analysis. The research subjects were principals, teachers, administrative staff, and principals of the Sarpras section of the school. The data collection technique used is the interview method, the observation method, and the documentation method, which will later obtain primary and secondary data for later analysis to get a conclusion. Based on the results of research that the author has carried out, it can be concluded that the management of infrastructure at SMP Negeri 8 Purworejo in supporting the learning process is quite good. However, several management of facilities and infrastructure have not been realized, including in the process of planning, procurement, use, maintenance, and elimination of infrastructure facilities. The obstacles experienced are the lack of human resources in the field of administration and infrastructure and the incoming funds for the procurement process and the infrastructure management process, which is still slow.